Surgical site infection rates in dialysis patients undergoing endovascular procedures. (October 2015) - Urbanes, Aris Q.; Litchfield, Terry; Graham, Kevin; Hutyra, Carolyn A.
Abstract: A surgical site infection (SSI) is an infection related to surgery that develops within 30 days after an operation or within 1 year of implant placement. Postoperative SSIs are the most common health‐care‐associated infections, occurring in up to 5% of surgical patients. Endovascular surgical procedures related to vascular access are common in the dialysis population and may cause SSIs. A large outpatient vascular access system developed and implemented a surveillance program to measure and monitor SSIs in their population. The health‐care surveillance system extended to 76 ambulatory care centers across the United States and Puerto Rico. Based on a recorded 92, 880 patient encounters, the surveillance system tabulated 12, 541 valid patient survey responses documenting self‐reported symptoms of infection within a 30‐day postoperative period. The SSI rate was tabulated based on the presence of two or more specified indicators of infection: antibiotics, pus, dehiscence, pain, warmth, and swelling. Patients undergoing interventional procedures received surveys at discharge. Data were collected and analyzed using SPSS software. Survey analysis indicated a less than 3% superficial incisional SSI rate in hemodialysis patients undergoing endovascular procedures. The SSI rate for clean wound procedures is generally 2% or less. These data indicate that dialysis patients undergoing interventional procedures in vascular access centers may have a slightly greater risk of developing SSIs due to the presence of additional risk factors including obesity, diabetes, and age. This study was limited by a set of loose diagnostic criteria self‐reported by patients, which may have overestimated the prevalence of infection. SSIs are a serious medical problem associated with increased morbidity and mortality and increased medical care costs. All providers should consider an active surveillance program following endovascular procedures given the comorbidities associated with the dialysis population.